LEARNING CHINESE THROUGH ENGLISH: TRANSLANGUAGING REALITY IN INDONESIAN HIGHER EDUCATION CFL CLASSROOM - Puspitasari, Titik; Yannuar, Nurenzia; Zubaidi, Nanang (Universitas Islam Sumatera Utara (UISU), 2024)
As Chinese popularity globally increases, the dynamics of multilingual Chinese classrooms are becoming more apparent in the field of language teaching. Following such trends, this study explores the phenomena of learning Chinese as a Foreign Language (CFL) through the English as Medium Instruction (EMI) in the context of Indonesian Higher Education. This study intends to contribute to the growing body of knowledge on translanguaging pedagogy and offer decision-makers and educators’ practical approaches for CFL training across a variety of linguistic situations. Through the use of a case study approach, this study investigates how CFL lecturers view and position translanguaging in their classes, as well as how such views are applied as they naturally occur in their CFL classes. Participating in this study are three native Chinese speakers of English who are limited to moderate competency in Indonesian and varied experiences in teaching CFL. The data are gathered through written teaching material examination and interviews. The results of this study show that lecturers are open to translanguaging options and positively perceive it and they use it either as explanatory strategy or managerial strategy in their CFL class. Even so, all three lecturers are aware that more careful consideration is still required due to its potential drawbacks and challenges.